Changes of RV-PC coupling during negative for myocardial ischemia dobutamine stress echocardiography. (3rd October 2022) - Koukos, M; Giannoulis, E; Solomou, E; Poulidakis, E; Dimitroglou, I; Patsourakos, D; Chatzigeorgiou, V; Liakos, C; Tsartsalis, D; Kalompatsou, A; Valatsou, A; Aggeli, C; et al.
Abstract: Background: Coupling between RV contractile function and pulmonary circulation (PC) reflects the comprehensive performance of the RV by integrating afterload and contractility. RV-PC coupling is nowadays frequently expressed by the non-invasively measured ratios TAPSE/RVSP and RVFWLS/RVSP. It has been shown that it decreases slightly during exercise, whereas no known data exist on how dobutamine does affect it. Purpose: The aim of this study was to evaluate the changes in RV-PC coupling and RV mechanics during the different stages of dobutamine stress echocardiography (DSE) in cases without known coronary artery disease (CAD) and negative for myocardial ischemia DSE. Methods: Patients with a low-to-intermediate risk for CAD were referred for and underwent DSE. RV systolic function was evaluated with TAPSE, S' and RV Free Wall (RVFW) Strain. The non-invasively measured RV-PC coupling was evaluated by indexing TAPSE and RV free wall longitudinal strain to right ventricular systolic pressure (RVSP) during baseline echocardiogram, low dose (inotropic dobutamine effect) and peak dose (chronotropic effect) stages of DSE. Results: Initially, a total of 53 patients underwent DSE. Eight patients had a positive for ischemia response and were excluded. The remaining 45 patients {mean age 65±8.7, 28 (63%) male}, 24 (53%) had hypertension, 24 (53%) were smokers, 33 (74%) had dyslipidemia, 15 (34%) had family history of CAD and 7 (15%) had diabetes mellitus. TAPSE, S' and RVFW Strain increased from baseline to peak dose [23.55±2.91 vs 28.76±1.9 (p<0.001), 13.13±1.79 vs 23.83±4.87 (p<0.001) and 19.7±5.87 vs 23.46±5.42 (p=0.044) respectively]. TAPSE/RVSP showed a significant steady decrease between baseline and low dose (0.88±0.14 vs 0.79±0.19) and peak dose (0.88±0.14 vs 0.74±0.12) stages with a difference of 0.09 (p value 0.013) and 0.14 (p value 0.000) respectively. On the other hand, RVFW Strain/ RVSP exhibited a significant decrease (0.60±0.15, p value 0.000) only between baseline and peak dose. There was no significant correlation of the change in TAPSE/RVSP with the change in E/E' or change in Systolic Blood Pressure. Conclusions: RV-PC coupling decreases during negative for ischemia DSE independently of LV dynamic changes and therefore, future studies should be oriented to evaluate the incremental role of this novel index not only for the assessment and evaluation of myocardial ischemia and RV disease that affects RV coupling, but also as a prognostic marker for patients with no evident ischemia. Funding Acknowledgement: Type of funding sources: None.